2016
DOI: 10.3389/fenvs.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anaerobic Digestion of Food Waste by Supplementing Trace Elements: Role of Selenium (VI) and Iron (II)

Abstract: This paper discusses the potential to enhance the anaerobic digestion of food waste FW by supplementing trace elements (Fe, Co, Ni, Zn, Mn, Cu, Se, and Mo) individually as well as in cocktails. A series of batch experiments on the biomethane potential of synthetic food waste were performed with low (FW-A) and high (FW-B) trace element background concentrations prepared in, respectively, Delft (The Netherlands) and Tampa (Florida, USA). The most effective trace elements for FW-A were Fe with an increase of 39.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…The model estimates that by supplementing the media with these metals, the SMA can be improved to values over 12 mLCH 4 .gCOD -1 .d -1 ( Figure 3B). Ariunbaatar et al (2016) verified an increase of 30-35% in CH 4 formation by adding 25-50 μg/L of Se. These authors reported that supplementation of Se resulted in a decrease of acetic and propionic acids in the batch assays.…”
Section: Synergic And/or Antagonist Effect Of the Two Negative Factormentioning
confidence: 66%
“…The model estimates that by supplementing the media with these metals, the SMA can be improved to values over 12 mLCH 4 .gCOD -1 .d -1 ( Figure 3B). Ariunbaatar et al (2016) verified an increase of 30-35% in CH 4 formation by adding 25-50 μg/L of Se. These authors reported that supplementation of Se resulted in a decrease of acetic and propionic acids in the batch assays.…”
Section: Synergic And/or Antagonist Effect Of the Two Negative Factormentioning
confidence: 66%
“…Measurement of biochemical methane potential (BMP) of organic substrates is important for research (Ariunbaatar et al, 2016;Yeshanew et al, 2016;Benn and Zitomer, 2018;Hafner et al, 2018;Filer et al, 2019) and biogas plant management (Koch et al, 2016;Gandiglio et al, 2017;Lippert et al, 2018). In contrast to nearly all chemical parameters (e.g., pH value and the chemical oxygen demand), and other biochemical parameters (e.g., biochemical oxygen demand), there is no standard method available for BMP tests (Baird et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Organic wastes from municipalities, agricultural and industrial activities degrade over a period of time, having a negative impact on the environment [1]. Landfilling of these wastes is still the most common practice in the world [2], resulting in pollution of water and soil with leachate, and air with emission of methane and other greenhouse gases [3,4]. Anaerobic digestion to produce biomethane has been a successful treatment option for these wastes; it is effective in solving environmental, health and energy challenges [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Landfilling of these wastes is still the most common practice in the world [2], resulting in pollution of water and soil with leachate, and air with emission of methane and other greenhouse gases [3,4]. Anaerobic digestion to produce biomethane has been a successful treatment option for these wastes; it is effective in solving environmental, health and energy challenges [3][4][5]. Additionally, the digestate residues from biogas plants are rich in macro-and micronutrients and also contain phosphorus and ammonium nitrogen [6], which make them suitable as biofertilizers [7].…”
Section: Introductionmentioning
confidence: 99%